Enhancing lecturer readiness to change: The mediation role of work engagement - Lista Meria; Corry Yohana; Unggul Purwohedi (Cogent Business & Management, 2023)
Organizational change is an inherent challenge that necessitates effective and appropriate management. The presence of human resources plays a pivotal role in the success of organizational change inside a business. Adapting and embracing change is crucial in effectively navigating and managing any change process. The present study examines the impact of psychological capital, perceived organizational support, and work engagement on predicting lecturer readiness to change. A convenience sampling method was employed to select 342 lecturers from private universities in Indonesia for this research. The data processing method uses SEM AMOS. The study results prove that psychological capital, organizational support, and work engagement can increase readiness to change. Then, work engagement can mediate the effect of psychological capital and organizational support on readiness to change. This research provides theoretical implications that work engagement can be an intermediary in increasing readiness for change, which is rarely studied. Furthermore, this study provides managerial implications and recommendations for further research.
Keywords: 650; organizational change; perceived organizational support; psychological capital; readiness to change; work engagement